PENERAPAN MODEL PEMBELAJARAN MAKE A MACTH UNTUK MENINGKATKAN HASIL BELAJAR IPA DI SD ISLAM DATOK SULAIMAN PALOPO KECAMATAN WARA KOTA PALOPO - Darmawati Darmawati (Institut Agama Islam Negeri Palopo, 2018)
This research reveals the subject matter concerning science learning result of third grade students at Datok Sulaiman Islamic Elementary School Palopo City. Thus, this study aims to determine the improvement of science learning outcomes that are applied through the use of Make a Macth model in third grade students of Islamic Elementary School Datok Sulaiman in Palopo City. This research uses qualitative and quantitative approach with Classroom Action Research (PTK) which is designed through two cycles. Research subjects, students of Islamic Elementary School Datok Sulaiman class III which amounted to 24 students. Data collection techniques used, namely observation, documentation, and tests. The research data obtained were analyzed by using descriptive statistic formula (percentage) to express descriptively the research result. Furthermore, to discuss and explain the results of research that is quantitative descriptive then used techniques of data reduction analysis, data presentation, and conclusion. From the research results found that in the prasiklus stage, with the average score of students' learning outcomes is 53.75 with 20% classical learning completeness. After implemented the learning by applying the Make a macth learning model, in the first cycle, the average value of science learning achievement is 63.75 with 50% classical learning completeness. Furthermore, in cycle II with the average value of increased interest in science learning is 75 with 66% complete classical learning. Thus, the improvement of science learning outcomes in class III Islamic elementary school Datok Sulaiman Palopo.